Using Highchart to Implement Business Intelligence on Attendance Assessment System based on YII Framework - Untung Rahardja (Pandawan Sejahtera Indonesia, 2022)
Today's students keep track of their attendance, and advisors can easily access that data. However, there are three (three) challenges that the advisor must overcome, one of which is submitting information in the form of a table that must be compared with great care and correctness.To facilitate the registration and measurement of advisor attendance for student advice An information form chart will be submitted by PenA (Attendance Assessment) using Highchart. Nim, Advisor, and Time of guidance are the information categories presented in the PenA (Attendance Assessment) chart. A comparison of the time guidance information in the chart may be used to assess how willingly the student is following the instructions.enA (Attendance Assessment) uses a Yii Framework-based website because it makes developing web apps easier and has a sufficient level of security.There are five (5) gains and one (1) deficit on PenA in this study (Attendance Assessment). It has been anticipated that PenA (Attendance Assessment) will improve the caliber of students' attendance in the University of Raharja's supervision procedure.